Characteristics of top management team and Chinese tax planning nexus: Findings from a fuzzy-set qualitative comparative analysis - Jiang, Haiming; Kim, Eunyoung (Frontiers in Psychology, 2022)
A top management team (TMT) has been identified as one of the key factors driving changes in tax planning strategy. Based on upper echelons theory, this study investigates whether configurations of TMT characteristics influence enterprise tax planning strategy by using the fuzzy-set qualitative comparative analysis (fsQCA). Using a panel data of China public companies, we found two configurations conducive to aggressive tax planning and two combinations conducive to low tax planning. Specifically, the level of education, tenure, age, career experience, and size of the top management team affect a firm’s propensity to engage in tax planning. Further, the results show that top management teams are not alike and highlight the differences in how these characteristics combine to impact tax planning.